The machinery of occupational safety and health policy in the European Union: history, institutions, actors - Vogel, Laurent (Brussels, 2015)
"This guide gives an overview of the background to, principle actors in, and essential tools of, EU occupational health and safety policy with the aim of contributing to a better understanding of this policy and of facilitating effective intervention at European level. It is aimed primarily at worker representatives responsible for health and safety at work and union officials involved in this area. It will also be useful to anyone with an interest in EU policy developments or involved in preventing occupational risks."